EVALUATION OF ANTIBACTERIAL ACTIVITY OF MEDICINAL PLANT EXTRACTS AGAINST CLINICAL ISOLATES OF PATHOGENS FROM CHILDREN WITH ACUTE GASTROENTERITIS AT KATUTURA STATE HOSPITAL¸ WINDHOEK, NAMIBIA - Iikasha, Albertina Mariina Ndinelao; Quaye, Isaac; Mumbengegwi, Davis (African Journal of Traditional, Complementary and Alternative Medicines, 2020)
Background: Diarrhea is a major health concern in Namibia with an estimate of 17000 cases in 2015 in Omusati and Kunene regions. The aims of this study were to isolate and identify gastrointestinal pathogens from stool samples of children admitted with acute gastroenteritis, and to determine the efficacy of selected medicinal plants used to treat gastroenteritis in Namibia. Materials and Methods: Stool samples were collected from children under five admitted to Katutura state hospital with acute diarrhea. Seeplex12 automated DNA extractor was used to extract bacterial DNA from the samples. PCR was used for bacteria identification. Medicinal plants Boscia albitrunca, Ziziphus mucronata, Combretum apiculatum, Solanum linnaeanum and Terminalia. sericea were collected, dried, ground and extracted using distilled water and ethanol. Plant extracts were screened for the presence of bioactive phytochemicals using TLC. Disc diffusion method was used to determine antibacterial activity of the plant extracts against the clinical bacteria isolates. Results: A total of 18 stool samples were collected and 12 samples were successfully identified by PCR. 33.3% were positive for Salmonella spp., 11.1% for E. coli 157:H7 VTEC and 22.2% for E.coli H7. C. apiculatum organic extracts exhibited potent antibacterial activity of (16± 0.57mm) at 1000 µg/ml against Shigella and Salmonella with a moderate minimum inhibitory concentration of 250 µg/ml against Salmonella. Salmonella and Shigella showed resistance to 10µg/ml of ampicillin. Conclusion: Plant extracts showed antibacterial activity against ampicillin resistant strains and E. coli 157:H7 VTEC, further tests to determine the toxicology and in vivo efficacy should be conducted.